2001
DOI: 10.1017/s1352465801001096
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Deliberate Self-Harm in Borderline Personality Disorder Using Dialectical Behaviour Therapy: A Pilot Study in a High Security Hospital

Abstract: Deliberate self-harm (DSH) presents a significant health problem, especially as treatments have not been particularly successful in reducing repetition. Dialectical behaviour therapy (DBT; Linehan, 1993) is one approach that has reported some success in reducing self-harm rates in borderline personality disorder patients, who self-harm frequently, though it remains largely untested outside its original setting. The present study aimed to assess the effectiveness of DBT in self-harming women in an institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 13 publications
3
71
0
Order By: Relevance
“…In a case study of an 18 year-old female with a two-year history of NSSI, Bauserman (1998) found that a year-and-half long treatment with DBT effectively eliminated the NSSI and led to improvements in problem-solving skills, coping, and interpersonal relationships. Low, Jones, Duggan, Power, and MacLeod (2001) reported that their use of DBT with 10 self-harming females diagnosed with BPD produced significant reductions in self-harm, and this reduction was maintained at 6-month follow-up. In addition, their clients experienced significant improvements in their coping beliefs, depressive symptoms, suicide ideation, and impulsiveness.…”
Section: Dialectical Behavior Therapy (Dbt)mentioning
confidence: 95%
“…In a case study of an 18 year-old female with a two-year history of NSSI, Bauserman (1998) found that a year-and-half long treatment with DBT effectively eliminated the NSSI and led to improvements in problem-solving skills, coping, and interpersonal relationships. Low, Jones, Duggan, Power, and MacLeod (2001) reported that their use of DBT with 10 self-harming females diagnosed with BPD produced significant reductions in self-harm, and this reduction was maintained at 6-month follow-up. In addition, their clients experienced significant improvements in their coping beliefs, depressive symptoms, suicide ideation, and impulsiveness.…”
Section: Dialectical Behavior Therapy (Dbt)mentioning
confidence: 95%
“…• Problem-solving skills training (seven studies) (Jones and McColl, 1991;Donnelly and Guy, 1998;Donnelly and Scott, 1999;McMurran et al, 1999;McGuire, 2000;Fleck et al, 2001;McMurran et al, 2001b); • Anger/Aggression management (four studies) (Stermac, 1986;Grant, 1999;McMurran et al, 2001c;Hilton and Frankel, 2003); • Deliberate self-harm interventions (two studies) (Low et al, 2001;Evershed et al, 2003); • Other (seven studies) (Rice, 1983;Beck-Sander et al, 1998;Tennant and Hughes, 1998;Moore et al, 2000;Donnelly et al, 2001;Jennings et al, 2002;Hodel and West, 2003).…”
Section: Focus Of Interventionsmentioning
confidence: 99%
“…Deliberate self-harm occurs in a variety of forms ranging from taking an overdose of prescribed or illicit drugs to cutting, burning and insertion (Low et al, 2001). Both Low et al (2001) and Evershed et al (2003) used Dialectical Behaviour Therapy (Linehan, 1993) as the intervention, in the former case with women with borderline personality disorder (BPD), a recognized feature of which is deliberate self-harm, and in the latter with men with BPD.…”
Section: Deliberate Self-harm Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various adaptations have been made to DBT to treat different patient populations: adolescents, in patients, British and Dutch patients, women with substance dependency, women veterans, male and female forensic patients and women with eating disorders (Barley 1993;Springer 1996;Miller 1997;Linehan 1999;Swales 2000;Koons 2001;Low 2001;Telch 2001;Evershed 2003;Verheul 2003). Generally, results have been encouraging and support the value of DBT in treating patients with borderline personality disorder.…”
Section: Who Does Dbt Work For?mentioning
confidence: 99%